If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 6 = 2x + -30 Reorder the terms: 6 + -2x = 2x + -30 Reorder the terms: 6 + -2x = -30 + 2x Solving 6 + -2x = -30 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 6 + -2x + -2x = -30 + 2x + -2x Combine like terms: -2x + -2x = -4x 6 + -4x = -30 + 2x + -2x Combine like terms: 2x + -2x = 0 6 + -4x = -30 + 0 6 + -4x = -30 Add '-6' to each side of the equation. 6 + -6 + -4x = -30 + -6 Combine like terms: 6 + -6 = 0 0 + -4x = -30 + -6 -4x = -30 + -6 Combine like terms: -30 + -6 = -36 -4x = -36 Divide each side by '-4'. x = 9 Simplifying x = 9
| 8r+4(r-7)=-2(3r+10) | | 5-8y+11y=-13+3 | | -4(x+1)=-2(8-x) | | (x+6)(x-8)=0 | | -55+6x+3x=3132 | | 12=8 | | (x+6)(x-8)(4x-3)=0 | | 6x+8=-4x+8 | | -3x+7=-14-6x | | y=80x+900 | | 188=-2+4(6x-8) | | -3x+3=2x-12 | | 6(4x+5)=2x | | -1+6x=17 | | 14x-2x^2=x | | 3m+3=m-5 | | 13x-7x+5x=-11 | | 8=4(3c+3) | | -10v=60 | | 2t-2=-2 | | 3x-3=2x-12 | | 5v^2+6v+7=v^2-4v | | 3d-12=-3 | | 0.4w-11=-0.5w | | 6+n=28+9 | | 2x+27=5x-3 | | r=50x-200 | | 188=-2x+4(6x-8) | | -8-3n=1 | | a+6=98 | | 3x+8=7x-12 | | 3x-2=2x-2 |